Clarifying a male color morph of Sphaerodactylus macrolepis Günther, 1859 and resolving the taxonomic confusion on Saint Croix - Griffing, Aaron H.; Keating, Shannon E.; Pinto, Brendan J.; Nielsen, Stuart V.; Gamble, Tony (Zootaxa, 2023)
Many species of sphaerodactyl gecko exhibit sexual dichromatism. In particular, dichromatism plays an important role in intersexual signaling for Sphaerodactylus. Furthermore, some species exhibit polymorphism in male color and pattern. Here, we describe a regional male color morph of Sphaerodactylus macrolepis from St. Croix. After generating both mitochondrial and nuclear phylogenies, we found that individuals with the St. Croix-specific yellow/orange head morph are part of the S. macrolepis clade. This distinct color morph likely contributed to the turbulent taxonomic history of the S. macrolepis species group. Given the documented diversity of the color patterns in this group and that sexual signals evolve rapidly, we suggest S. macrolepis is an excellent group to study the ecological and evolutionary consequences of dichromatism and polymorphism.